Humoral and cell-mediated immunity in large non-toxic multinodular goitre - Mota, N. G S; Kiy, Y.; Rezkallah-Iwasso, M. T.; Peracoli, M. T S (My University, 1980)
Humoral and cell-mediated immunity was investigated in fourteen patients with non-toxic multinodular goitre and ten healthy controls by in vitro methods. These included determination of sheep erythrocyte and complement rosette-forming cells in the peripheral blood, immunoglobulin levels, titres of thyroglobulin and microsomal antibodies and migration inhibition test using thyroid extract and phytohemagglutinin. When compared with controls the patients showed high IgA levels and positive response to thyroid antigen in the leucocyte migration inhibition test. There was no correlation between the leucocyte migration results and the presence of auto-antibodies. These findings indicate a possible role of cell-mediated immunity in non-toxic multinodular goitre.
Keywords: autoantibody; blood and hemopoietic system; cellular immunity; endocrine system; goiter; humoral immunity; in vitro study; leukocyte migration; major clinical study; t lymphocyte; Adult; Aged; Antibody Formation; Cell Migration Inhibition; Goiter, Nodular; Human; Immunity, Cellular; Immunoglobulins; Leukocytes; Middle Age; Rosette Formation